Impact of coronary artery disease on in-hospital mortality in patients with aortic valve disease - Höllriegel, Robert; Linke, A.; Hochadel, Matthias; Schuler, G.; Kerber, S.; Hambrecht, R.; Grube, E.; Hauptmann, K.E.; Zahn, R.; Zeymer, U.; Senges, Jochen (Herz, 2013)
Although aortic valve disease (AVD) is frequently associated with coronary artery disease (CAD), little is known about the impact of significant coronary artery disease on mortality after diagnostic cardiac catheterization in patients with AVD.
Gesehen am 29.06.2021